The Map to Everywhere - Ryan, Carrie; Davis, John Parke; Harris, Todd (New York : Little, Brown & Company, 2014)
Twelve-year-old Fin, a master thief from the pirate world of Khaznot Quay, and Marrill, also twelve, of Arizona, cross paths in the magical world of the Pirate Stream while on a quest for a mysterious map.
Keywords: Adventure stories; Pirates -- Juvenile fiction; Wizards -- Juvenile fiction; Theft -- Juvenile fiction; Magic -- Juvenile fiction; Maps -- Juvenile fiction; Adventure and adventurers -- Fiction; Pirates -- Fiction; Wizards -- Fiction; Stealing -- Fiction; Magic -- Fiction; Maps -- Fiction; Fantasy